Rumination focused cognitive-behavioral therapy for managing rumination in job-seeking young adults with depression: A single-case study - Nur Harwiningtyas, Annisa; Wahyu Yuniarti, Kwartarini (Psychological Research and Intervention, 2024)
Unemployed individuals are highly susceptible to depressive disorders that impact their cognitive dynamics. Rumination, commonly observed in individuals with depressive disorders, reinforces depressive affect. Addressing rumination is crucial for cognitive management, ultimately alleviating depressive symptoms. This single-case study investigates the effectiveness of rumination-focused cognitive-behavioral therapy (RFCBT) on a 24-year-old unemployed female. Assessments involved interviews, observations, the PHQ-9, and EPPS, followed by 10 intervention sessions, including 8 therapy sessions. Post-intervention results, measured using the Reliability Change Indicator (RCI) on pre-and post-treatment PHQ-9 scores, demonstrated a significant score reduction of 17 points (89.47%). Descriptive data from semi-structured interviews corroborated these findings.